PLIDe: Implementation of VARK Theory and HCI Design Laws in Python Programming Language Instructional Design Application - Rahmat, Hazwani; Haikal Aizuddin Nasruddin,; Muhammad Noor Azmeer Abdul Halim,; Nur Liyana Insyirah Mohd Barsrah, (Multidisciplinary Applied Research and Innovation, 2025)
The platform aims to suit diverse learning styles and improve understanding and skills in Python programming. Common problems include inadequate support for a variety of learning styles and a lack of effective integration of instructional design learning materials. The goals are to create mobile apps with flexible learning styles, assess the UI and resources of PLIDe, and provide learning materials for the Python language. The study follows the ADDIE methodology (analysis, design, development, implementation, evaluation) and was assessed using CSUQ and LORI surveys with students and lecturers at Universiti Tun Hussein Onn Malaysia (UTHM). PLIDe effectively builds coding understanding and competence.